Clinical and Diagnostic Indices of Cerebral Blood Flow in Patients with Cervical Spine Diseases - Aziza Jurabekova; Shohsanam Eshimova; Janna Nazarova; Nigora Alikulova; Nargiza Abdullaeva (International Journal of Medical Toxicology and Legal Medicine, 2024)
In 88 patients, ultrasound duplex and magnetic resonance angiography of the arterial and venous sections of the vascular bed of the head and neck were performed, and it was shown that in degenerative diseases of the cervical spine (CS), along with changes in the arterial blood flow, changes in the regulation of venous circulation are also indicative. Aim: Study of cerebral venous blood flow in cervical spinal injuries. Materials and methods:A total of 88 patients with degenerative changes in the cervical spine were examined, who were treated in the neurological department of the clinic of the Samarkand Medical University from 2022 to 2024. Comprehensive diagnostics using modern methods such as magnetic resonance angiography (MRA), rheoencephalography (REG), and Doppler ultrasonography of the cerebral vessels were performed for each patient. Results and discussions:It has been found that various disorders in the cervical spine cause changes in arterial blood flow and regulation of venous outflow from the skull. Conclusion:Thus, various disorders in the cervical spine cause changes in arterial blood flow and regulation of venous outflow (VO). Expansion of the IJV and a decrease in blood flow intensity are often associated with degenerative changes in the cervical spine.